Decision-making practice during coaching sessions in elite youth football across European countries - Roca, A.; Ford, P. R. (Science and Medicine in Football, 2020)
We examined the practice activities employed by 53 youth football coaches working in youth academy professional top-division clubs from England, Germany, Portugal, and Spain. This is the first study to explore the microstructure of coach-led practice in elite youth football across multiple countries. A total of 83 practice sessions from under-12 to under-16 age groups was collected in situ. Sessions were analysed for the proportion of time in `non-active decision-making` (e.g., unopposed technical or tactical skills practices, fitness training) and `active decision-making` activities (e.g., small-sided games, skills practice with opposition), with the latter deemed superior for the transfer of game intelligence skill to match play. More time was spent in active decision-making (M = 62%) compared to non-active decision-making activities (M = 20%) and transitioning between activities (M = 17%). Players from Portugal and Spain spent a higher amount of time in active decision-making activities compared to English and German players, whereas, English players spent more time in unopposed technical-based drills and German players in improving fitness aspects of the game without the ball. Findings extend previous research assessing coach-led youth football practice in single countries by demonstrating differences in training activities between countries in Europe.